Analisis Efektivitas Mesin Cetak Flexo menggunakan Metode Overall Equipment Effectiveness Berbasis Six Big Losses: Studi Kasus: Industri Corrugated Box - Saw Shu Zhen, Angelica Audrey; Purnomo, Purnomo; Ekawati, Yurida (Teknik Industri Universitas Ma Chung, 2024)
PT X is a manufacturing company operating in the integrated cardboard industry, utilizing various machines, including flexography machines. This study aims to analyze the primary causes of production deficiencies in the flexography process and provide improvement recommendations using the Six Big Losses-based Overall Equipment Effectiveness (OEE) method. The OEE analysis revealed that the average availability ratio is 88.8%, falling short of the world-class standard of 90%. A deeper analysis using the Six Big Losses methodology identified that the primary cause for not achieving the desired availability ratio is the high percentage of setup and adjustment losses, which stands at 7%. To address these issues, several recommendations are proposed. Firstly, conducting comprehensive training for operators on the proper and correct operation of flexography machines is essential. This training will enhance their technical skills and reduce the time lost during setup and adjustments. Secondly, implementing daily briefings for operators before shifts begin, coupled with regular supervision, will ensure consistent adherence to operational standards. Moreover, establishing a routine and time-limited cleaning schedule for machines and work locations will minimize unexpected downtimes due to maintenance issues. Finally, developing and enforcing standardized machine operation protocols will promote discipline among operators, ensuring that all procedures are followed meticulously. These recommendations aim to improve the overall efficiency of flexography machines, thereby increasing the availability ratio to meet or exceed the world-class standard. By addressing the root causes of production inefficiencies, PT X can enhance its operational performance and maintain its competitive edge in the cardboard industry.